Vitiligo expansion and extent correlate with durable response in anti‐programmed death 1 antibody treatment for advanced melanoma: A multi‐institutional retrospective study. Issue 6 (10th April 2020) - Matsuya, Taisuke; Nakamura, Yasuhiro; Matsushita, Shigeto; Tanaka, Ryota; Teramoto, Yukiko; Asami, Yuri; Uehara, Jiro; Aoki, Megumi; Yamamura, Kentaro; Nakamura, Yoshiyuki; Fujisawa, Yasuhiro; Livingstone, Elisabeth; et al.
Abstract: Vitiligo is an autoimmune disorder resulting from the destruction of melanocytes. Several reports indicate the association between vitiligo and treatment response in advanced melanoma during immunotherapy. It has not been investigated, however, if an increase of vitiligo while on treatment with anti‐programmed death 1 (PD‐1) antibodies is associated with more durable responses. The aim of this study is to evaluate the correlation between the vitiligo dynamics and clinical efficacy of anti‐PD‐1 antibodies. This study included advanced melanoma patients who were treated with nivolumab or pembrolizumab and developed vitiligo thereafter. Correlation between vitiligo expansion (defined as an increase of lesion size at two separate time points at least 4 weeks apart) as well as vitiligo extent (body surface area [BSA] affected) and clinical efficacy based on response rate, progression‐free survival and overall survival was assessed. We retrospectively reviewed 29 patients. The median time from the initiation of anti‐PD‐1 antibody to vitiligo onset was 4.3 months in patients who showed a response and 5.5 months in patients who showed no response ( P  = 0.31). Twelve patients showed vitiligo expansion, and in nine of these patients, vitiligo increased to grade 2 (covering ≥ 10% BSA). Vitiligo expansion and grade 2 vitiligo showed no improvement in treatment response ( P  = 0.59 and 0.25) but were associated with prolonged progression‐free survival ( P  = 0.019 and 0.04). Grade 2 vitiligo also showed a trend for prolonged overall survival ( P  = 0.07). Trend of expansion and larger vitiligo extent may be predictive factors of prolonged survival during anti‐PD‐1 antibody in melanoma patients.